Atık Mısır Koçanı Takviyeli Polyester Kompozit Üretimi ve Karakterizasyonu - Orhan, Ramazan; Aydoğmuş, Ercan (Osman SAĞDIÇ, 2022)
Bu çalışmada atık mısır koçanları öğütülerek polyester kompozitte kullanılmıştır. Laboratuvar koşullarında dolgu maddesi olarak doymamış polyester (UP) içerisine karıştırılarak homojen dağılım sağlanır. Daha sonra karışıma metil etil keton peroksit (MEKP) ve kobalt oktoat (Co Oc) katalizörleri eklenir. Belirli miktarlarda kullanılan katkı ve dolgu maddeleri kısa süre karıştırıldıktan sonra polyester kompozitler standart kalıplara dökülerek kürlenmesi için beklenir. Kürleme sonrası elde edilen kompozitin yoğunluğu, Shore D sertliği ve termal bozunma davranışı incelenmiştir. Karışımdaki mısır koçanı miktarı arttıkça polyester kompozitin yoğunluğu azalır. Ayrıca karışımdaki dolgu maddesinin oranının artması polyester kompozitin gözenekliliğini de artırmaktadır. Isıl iletkenlik ölçümlerinde, artan dolgu miktarına göre polyester kompozitin ısıl iletkenlik katsayısının az da olsa arttığı görülmektedir. Ayrıca mısır koçanı takviyesi, polyester kompozitin hem Shore D sertliğini hem de aktivasyon enerjisini azaltmaktadır. Elde edilen sonuçlara göre ağırlıkça % 3'ün üzerinde mısır koçanı takviyesi kullanımının kompozitin yüzey morfolojisini ve mekanik özelliklerini olumsuz yönde etkilediği görülmüştür. Ekonomik ve hafif bir polyester kompozit elde edilirken hem termal hem de mekanik özelliklerin zayıflamaması için dolgu miktarına dikkat edilmelidir.

In this study, waste corncobs are ground and used in the polyester composite. Homogeneous distribution is provided by mixing it into unsaturated polyester (UP) as a filler under laboratory conditions. Then, methyl ethyl ketone peroxide (MEKP) and cobalt octoate (Co Oc) catalysts are added to the mixture. After mixing the additives and fillers used in certain amounts for a short time, the polyester composites are poured into standard molds and waited for curing. The density, Shore D hardness, and thermal decomposition behavior of the composite obtained after curing have been investigated. As the amount of corncob in the mixture increases, the density of the polyester composite decreases. Besides, the rise in the ratio of this filler in the mixture also increases the porosity of the polyester composite. In the thermal conductivity measurements, it is seen that the thermal conductivity coefficient of the polyester composite increases, albeit slightly, according to the increasing amount of filler. Also, corncob reinforcement reduces both Shore D hardness and activation energy of the polyester composite. According to the results obtained, it was observed that the use of corncob reinforcement above 3 wt.% negatively affected the surface morphology and mechanical properties of the composite. While obtaining an economical and light polyester composite, attention should be paid to the amount of filler so that both thermal and mechanical properties are not weakened.
Production and Characterization of Waste Corncob Reinforced Polyester Composite
Keywords: Engineering; Mühendislik